2023
DOI: 10.1002/cbic.202200719
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Bio‐epoxidation of Unactivated Alkenes

Abstract: Optically active epoxides play important roles in pharmaceutical, agricultural and fine chemical syntheses. There are many chiral medications with pharmacodynamic activity in nature that can be synthesized by chiral epoxides. In recent years, researchers have developed a variety of biocatalysts for the asymmetric epoxidation of alkenes, which use oxygen or hydrogen peroxide as eco-friendly and low-cost oxidants, to provide better chemo-, regio-and stereoselectivity under moderate reaction conditions. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
0
1
0
Order By: Relevance
“…Taken together, we propose the formation mechanism of 1,4-dihydroxy- p -menth-2-ene from terpinen-4-ol via epoxide and diol intermediates ( Fig. S9 ) as described previously [ 49 , 64 ]. We suggest that the mono-hydroxylated product is produced through intermediate epoxidation and that engineered CYP102A1 can be applied to biotechnology industries as a biocatalyst for the production of terpene derivatives.…”
Section: Discussionsupporting
confidence: 80%
“…Taken together, we propose the formation mechanism of 1,4-dihydroxy- p -menth-2-ene from terpinen-4-ol via epoxide and diol intermediates ( Fig. S9 ) as described previously [ 49 , 64 ]. We suggest that the mono-hydroxylated product is produced through intermediate epoxidation and that engineered CYP102A1 can be applied to biotechnology industries as a biocatalyst for the production of terpene derivatives.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, NbC materials were utilized in electrocatalysis and photocatalysis while there are only a few investigations on its application in chemical catalysis . Previously coordinatively unsaturated niobium species have been proven to be the key active sites in epoxidation reactions, which is of great importance in the synthetic chemistry because epoxides are widely used as the intermediates in the production of pharmaceuticals, surfactants, and ester chemicals, especially in the utilization of CO 2 into cyclic carbonates. , Other non-niobium catalysts for the epoxidation reaction have also been reported such as TiO x supported on or co-condensed with SiO 2 , MoO 3 nanoparticles, and so on. Recently, Bregante et al demonstrated that niobium-silica catalysts, specifically the Nb-substituted framework of zeolites, reveal the highest activity and selectivity of the desired epoxide products across all of Groups 4 and 5 .…”
Section: Introductionmentioning
confidence: 99%